1994
DOI: 10.4049/jimmunol.153.4.1789
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine dehydrogenase and xanthine oxidase activity and gene expression in renal epithelial cells. Cytokine and steroid regulation.

Abstract: Reactive oxygen species have been implicated in the tissue injury and loss of epithelial barrier function associated with a number of clinical disorders in which disregulated inflammation seems to be a dominant event, such as endotoxemia and viral syndromes. In these disorders, xanthine oxidase (XO) contained within the epithelial cell has been proposed as a major source of injurious reactive oxygen species. This study was undertaken in an effort to understand the regulation of xanthine dehydrogenase (XDH)/XO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Numerous pathological stimuli including pro-inflammatory cytokines [ [47] , [48] , [49] ], unhealthy diet [ 50 ], cigarette smoke [ 51 ], hypoxia [ 52 , 53 ], ischemia-reperfusion injury and CVD risk factors (such as hypertension [ 54 ]) increase XOR expression and activity. These stimuli also promote the conversion of XOR from the housekeeping reduced isoform, XDH, to the more detrimental oxidized isoform, XO.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pathological stimuli including pro-inflammatory cytokines [ [47] , [48] , [49] ], unhealthy diet [ 50 ], cigarette smoke [ 51 ], hypoxia [ 52 , 53 ], ischemia-reperfusion injury and CVD risk factors (such as hypertension [ 54 ]) increase XOR expression and activity. These stimuli also promote the conversion of XOR from the housekeeping reduced isoform, XDH, to the more detrimental oxidized isoform, XO.…”
Section: Discussionmentioning
confidence: 99%
“…Our research showed that these cytokines mRNAs were regulated by C1QBP in RCC cells. Inflammatory cytokines TNF-α, IL6, IL-1β, and IFN-γ have been reported to promote the transcription of XDH [18]. Therefore, we speculated that C1QBP might promote XDH transcription by regulating the expression of these inflammatory cytokines (TNF-α, IL6, and IFN-γ), resulting in ROS production and subsequent induction of apoptosis of RCC cells.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of XDH is affected by many factors, including inflammatory cytokines, hormones, growth factors, stimuli, etc [14]. Inflammatory cytokines TNF-α, IL6, IL-1β, and IFN-γ have been reported to promote the transcription of XDH [18]. To examine whether C1QBP affects transcriptional stimulators of XDH, we measured the TNF-α, IL6, IL-1β, and IFN-γ mRNA.…”
Section: C1qbp Modulates Xdh Mrna At Translational Levelmentioning
confidence: 99%
“…Numerous pathological stimuli including pro-inflammatory cytokines (5052), unhealthy diet (53), cigarette smoke (13), hypoxia (14,54), ischemia-reperfusion injury and CVD risk factors (such as hypertension (55)) increase XOR expression and activity. These stimuli also promote the conversion of XOR from the housekeeping reduced isoform, XDH, to the more detrimental oxidized isoform, XO.…”
Section: Discussionmentioning
confidence: 99%